Analysis of the Disintegrin-metalloproteinases Family Reveals ADAM29 and ADAM7 Are Often Mutated in Melanoma - Wei, Xiaomu (2011)
We performed a mutational analysis of the 19 disintegrin-metalloproteinases (ADAMs)genes in human cutaneous metastatic melanoma and identified eight to be somatically mutated in 79 samples, affecting 34% of the melanoma tumors analyzed. Functional analysis of the two frequently mutated ADAM genes, ADAM29 and ADAM7 demonstrated that the mutations affect adhesion of melanoma cells to specific extracellular matrix proteins and in some cases increase their migration ability. This suggests that mutated ADAM genes could play a role in melanoma progression.